Social Media Marketing Game Theory and the Emergence of Collaboration - Anderson, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Does social media marketing signal the death of advertising, or its rebirth? Or is it merely the trend of the moment, destined for over-saturation and burnout? The current mania for social media clouds the marketer's vision with both overheated hype and dire predictions, none of which brings us closer to understanding how and why social media has emerged as a driving force in contemporary marketing.The science of game theory provides the toolset for the marketer and the marketing scholar to see past the bubble trends to the deep structure of marketer-consumer relationships. Originally developed to guide Cold-War geopolitical maneuvering, game theory illuminates the conflicting and overlapping interests of marketers and consumers in marketing's long and contentious evolution toward cooperation. Social media marketing is revealed as an evolutionary stage in a movement that began with the Web itself. Its future depends on the decisions marketers make today.
Surviving the Customer -- Zero-Sum Games in Traditional Marketing -- The Prisoner$1 (Bs Dilemma and the Emergence of Cooperation -- Consumer Revolt and the Rising Cost of Defection -- Sustaining Marketer-Consumer Cooperation through Coordination Games -- Crowdsourcing and Schelling$1 (Bs Theory of Self-Command -- Content Popularity and Spence$1 (Bs Theory of Costly Signaling -- Kapferer$1 (Bs Prism and the Shifting Ground of Brand Identity -- Maxwell$1 (Bs Demon and the Dwindling Supply of Consumer Attention.s
Keywords: Economics; Economics, Mathematical; Marketing; Mass media; Economics/Management Science; Marketing; Game Theory/Mathematical Methods; Media Management